Recent Trends in the Argumentation of the European Court of Human Rights on Children’s Rights - Ágnes Lux (Public Governance, Administration and Finances Law Review)
The European Convention on Human Rights (ECHR) is a key human rights treaty ratified by all EU member states and beyond. Although it does not focus specifically on children, it includes relevant provisions and obliges states to protect the rights of all individuals, including children. Moreover, the UN Convention on the Rights of the Child (UN CRC) is ratified by all ECHR member states, which presumably contributed to the greater focus to the increase of child rights reasoning. This paper explores how ECHR provisions – particularly Article 8 on the right to privacy and family life, Article 3 on the prohibition of torture and other forms of cruel, degrading treatment, and Article 14 on non-discrimination – and recent European Court of Human Rights (ECtHR) rulings contribute to the wider protection of children’s rights, analysing their use as rhetorical arguments in legal reasoning.